Distributional implications of the crisis in Greece in 2009 - 2012 - Chrysa Leventi; Manos Matsaganis (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The severe economic crisis affecting Greece since 2009 is having an unprecedented impact in terms of job and income losses, and is widely perceived to have a comparably significant effect in terms of greater inequality and increased poverty. We provide an assessment of whether (and to what extent) the latter is the case. More specifically, we use the European tax-benefit microsimulation model EUROMOD in order to quantify the impact of the austerity (i.e. fiscal consolidation policies) and the recession (i.e. negative developments in the wider economy) on the distribution of incomes in 2009-2012, and estimate how the burden of the crisis has been shared across income groups. We conclude by discussing the policy implications of our research.
Keywords: C81; I3; H55; 330; austerity; Greece; poverty; inequality; microsimulation